2016
DOI: 10.1016/j.imr.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antioxidant, antimicrobial activities and chemical profiles of three coffee (Coffea arabica L.) pulp aqueous extracts

Abstract: BackgroundThis study explored the bioactivities and nutrient compositions of coffee (Coffea Arabica L.) pulp which was prepared in three different ways [Coffee Pulp Extracts (CPE) 1–3].MethodsThe coffee pulp was prepared in three different ways by distinct selecting and freezing processes. The nutritional values, polyphenol contents, antioxidant activity, and antibacterial properties of the coffee pulp as well as the characterization of the active ingredients by liquid chromatography-electrospray ionization-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 26 publications
4
77
1
11
Order By: Relevance
“…Whereas coffee husk and coffee pulp have great potential as a functional food ingredient (SETYOBUDI et al, 2019) due to its components contained such as of proteins (8 % to 11 %), lipids (0.5 % to 3 %), minerals (3 % to 7 %), carbohydrates (58 % to 85 %), reducing sugars (14 %), caffeine (~1 %), and tannin (~5 %) and 0.2 mg g −1 to 1.9 mg g −1 of 5-O-caffeoylquinic acid compound, the main phenolic compound found in Arabica and Robusta coffee (FRANCA, OLIVEIRA, 2009;MULLEN et al, 2013). Some of the studies that have been conducted to utilize coffee husk as a dietary fiber ingredient (BENITEZ et al, 2019), a food supplement (ESQUIVEL, JIMÉNEZ, 2012;BLINOVÁ, L. et al, 2017); an antioxidant and anti-bacterial (MURTHY et al, 2012;DUANGJAI et al, 2016). Although there are relatively many studies on cookie recipes (CF GLOBAL HOLDINGS, 2019), research on coffee cherry flour (CCF) as a functional food has never been found Cookies, one type of pastry, is very popular for Indonesian people.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas coffee husk and coffee pulp have great potential as a functional food ingredient (SETYOBUDI et al, 2019) due to its components contained such as of proteins (8 % to 11 %), lipids (0.5 % to 3 %), minerals (3 % to 7 %), carbohydrates (58 % to 85 %), reducing sugars (14 %), caffeine (~1 %), and tannin (~5 %) and 0.2 mg g −1 to 1.9 mg g −1 of 5-O-caffeoylquinic acid compound, the main phenolic compound found in Arabica and Robusta coffee (FRANCA, OLIVEIRA, 2009;MULLEN et al, 2013). Some of the studies that have been conducted to utilize coffee husk as a dietary fiber ingredient (BENITEZ et al, 2019), a food supplement (ESQUIVEL, JIMÉNEZ, 2012;BLINOVÁ, L. et al, 2017); an antioxidant and anti-bacterial (MURTHY et al, 2012;DUANGJAI et al, 2016). Although there are relatively many studies on cookie recipes (CF GLOBAL HOLDINGS, 2019), research on coffee cherry flour (CCF) as a functional food has never been found Cookies, one type of pastry, is very popular for Indonesian people.…”
Section: Introductionmentioning
confidence: 99%
“…Conditions for ESI-Q-TOF-MS were the same as in the previous study (Duangjai et al, 2016). A 6540 ultrahigh definition accurate mass Q-TOF (Agilent Technologies, Palo Alto, CA, USA) was converted into an Agilent 1260 infinity high performance liquid chromatography instrument (Agilent, Waldbonn, Germany) via an ESI interface.…”
Section: Identification Of Proanthocyanidins In Hkd Rice Bran Extractmentioning
confidence: 99%
“…Polyphenols different from anthocyanins, such as phenolic acids (147.4-492.7 g/kg), gallic acid 4 (93.1-353.7 mg/kg), and flavonoids (2.52-13.5 mg/kg), were obtained with acidified methanol from residues of grape (Vitis vinifera L.) seed oil production [28], while protocatechuic acid 1 and chlorogenic acid 14 were extracted with hot water (92 AE 3°C, 2 min) [13]. Other solvents used for EP extraction are acetone/water mixtures (80%, 3 h stirring) to obtain flavonol 37, 40 glycosides and xanthones 17-18 from lyophilized mango peels ( Table 1 and Figure 2) [31].…”
Section: Ars Extractionmentioning
confidence: 99%
“…Antioxidant Compounds from Agro-Industrial Residue DOI: http://dx.doi.org /10.5772/intechopen.85184 mainly pomace, peels, seeds, and fibers from fruits such as acerola (Malpighia) [12], coffee [13], mandarin oranges (Citrus) [14], berries [15], yuzu (Citrus) [16], mangoes [17], apples [3], pears [3], oranges [18], jocote (Spondias purpurea L.) [19], cocoa husks [20], and grapes [21].…”
mentioning
confidence: 99%